2008
DOI: 10.1016/j.catena.2007.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Sand detachment under rains with varying angle of incidence

Abstract: In the case of wind-driven rain, as the angle of rain incidence increases, greater force components act parallel to the surface and lower force components act perpendicular to the surface. Therefore, raindrop impact angle could influence the detachment process in the existence of substantial lateral jet development. This could be particularly significant for a cohesionless sand surface that has a weaker resistance to the dislodgement by a raindrop impact than a soil surface. Experiments of simulated wind-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Comparing these data with natural rainfall data in windy conditions simulated by Erpul et al (2008), it is found that the energy distribution in this study are close to the data under the condition of working pressure of 100 kPa and 150 kPa, with a 6.4 m/s wind speed. In Erpul's trial, the amounts of sediment formation under the above conditions are very Comparison between sprinkler irrigation and natural rainfall rigation, especially in sandy loam and silt loam.…”
Section: Kinetic Energy Analysis Of Sprinkler Droplets Of Precipitatisupporting
confidence: 79%
See 1 more Smart Citation
“…Comparing these data with natural rainfall data in windy conditions simulated by Erpul et al (2008), it is found that the energy distribution in this study are close to the data under the condition of working pressure of 100 kPa and 150 kPa, with a 6.4 m/s wind speed. In Erpul's trial, the amounts of sediment formation under the above conditions are very Comparison between sprinkler irrigation and natural rainfall rigation, especially in sandy loam and silt loam.…”
Section: Kinetic Energy Analysis Of Sprinkler Droplets Of Precipitatisupporting
confidence: 79%
“…[1]-[3] are used to compute SP and its directional components (Erpul et al, 2008): test data for estimating terminal velocity. The most commonly used form is the power function (Atlas & Ulbrich, 1977;Ulbrich, 1983):…”
Section: Movement Characteristics Of Natural Rainfallmentioning
confidence: 99%
“…Soil detachment significantly changes with windward and leeward slopes under wind-driven rains This means that, apart from the transport capacity of the overland flow, the delivery of the detached particles to the flow will be different when the rainfall is upstream-moving from when it is downstream-moving (Erpul, 2003a(Erpul, , 2005(Erpul, , 2008. In fact the experiments do not entirely represent wind-driven rains.…”
Section: Laboratorial Proceduresmentioning
confidence: 99%
“…In some cases comparison has been made for the soil loss associated with these storms (e.g., Erpul et al, 2003Erpul et al, , 2005de Lima et al, 2008;Erpul et al, 2008). Nevertheless, the influence of storm movement on water erosion has received much less attention than has overland flow.…”
Section: Introductionmentioning
confidence: 98%